2016
DOI: 10.1007/s11764-016-0560-5
|View full text |Cite
|
Sign up to set email alerts
|

Employment implications of informal cancer caregiving

Abstract: Purpose Previous research describing how informal cancer caregiving impacts employment has been conducted in small samples or a single disease site. This paper provides population-based estimates of the effect of cancer caregiving on employment and characterizes the employment changes made by caregivers. Methods The sample comprised cancer survivors with a friend or family caregiver, participating in either the Medical Expenditure Panel Survey Experiences with Cancer Survivorship Survey (ECSS) (n=458) or the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
63
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(82 citation statements)
references
References 27 publications
(48 reference statements)
16
63
3
Order By: Relevance
“…In our study, patients treated with chemotherapy were more likely to adversely affect the employment status of their caregivers. This is consistent with several existing studies [22,35], which found that for FCGs whose patients were treated with chemotherapy, the probability of altered employment status was higher than those not treated with chemotherapy. Compared to other therapy methods, chemotherapy might be viewed as a catastrophe for both patients themselves and their families due to the long duration and recovery period, combined with more burdensome symptoms and poor prognosis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, patients treated with chemotherapy were more likely to adversely affect the employment status of their caregivers. This is consistent with several existing studies [22,35], which found that for FCGs whose patients were treated with chemotherapy, the probability of altered employment status was higher than those not treated with chemotherapy. Compared to other therapy methods, chemotherapy might be viewed as a catastrophe for both patients themselves and their families due to the long duration and recovery period, combined with more burdensome symptoms and poor prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…FCGs of patients with limited ability to perform physical or mental tasks were also more likely to experience employment changes in our study. Although our ndings are inconsistent with that from Sherwood et al, who indicated that FCGs' employment condition was not in uenced by the patient's ability, our results are in agreement with other previous studies [22,38]. Loss of ability to perform tasks is important because it is an indicator of poor physical and mental health.…”
Section: Discussioncontrasting
confidence: 55%
“…This is comparable to de Moor's study, which found that 25% of cancer survivors' caregivers made extended employment changes and 12% of caregivers were not employed. 40 This burden often falls on family caregivers in rural areas because of their F I G U R E 4 After treatment, did cancer interfere with your ability to perform any physical tasks required by your job? A, Women; B, men (There are three work groups (stopped working, reduced work hours, and no change in work hours) by their ability to perform physical tasks.).…”
Section: F I G U R E 3 Changes In Work Hoursmentioning
confidence: 99%
“…The LIVESTRONG (LS) Foundation developed the Survey for People Affected by Cancer to ascertain how cancer has affected the lives of cancer survivors. To develop this survey, LS coordinated with the National Cancer Institute, the Office of Behavioral and Social Sciences Research, the Centers for Disease Control and Prevention, the American Cancer Society, and the Agency for Healthcare Research and Quality to include elements of the Experiences with Cancer Survivorship supplement of the Medical Expenditures Panel Survey . More information about the survey can be found on the LS Foundation's website (https://www.livestrong.org/what-we-do/our-research.…”
Section: Introductionmentioning
confidence: 99%
“…To develop this survey, LS coordinated with the National Cancer Institute, the Office of Behavioral and Social Sciences Research, the Centers for Disease Control and Prevention, the American Cancer June 1, 2019 Cancer Society, and the Agency for Healthcare Research and Quality to include elements of the Experiences with Cancer Survivorship supplement of the Medical Expenditures Panel Survey. 8 More information about the survey can be found on the LS Foundation's website (https://www.livestrong.org/what-we-do/our-research. Accessed January 16,2019) and related publications on the population of the original LS survey.…”
Section: Introductionmentioning
confidence: 99%